DNAzymes: Selected for Applications. Issue 3 (25th January 2018) - Morrison, Devon; Rothenbroker, Meghan; Li, Yingfu
Abstract: DNA‐based enzymes, also known as deoxyribozymes or DNAzymes, are single‐stranded DNA molecules with catalytic activity. DNAzymes do not exist in nature but can be isolated from random‐sequence DNA pools using in vitro selection. To date, many DNAzymes that collectively catalyze a diverse range of chemical transformations have been reported. Here, examples of new DNAzymes engineered to mimic some intriguing functions of naturally occurring protein‐based enzymes are discussed. This is followed by discussions of recent examples of a particular class of DNAzymes, known as "RNA‐cleaving DNAzymes", that have been derived specifically so that their activity is strictly dependent on a given chemical or biological stimulus. Some unique ways to employ ligand‐responsive DNAzymes for the design of bioanalytical assays and biosensors are then highlighted. Being DNA molecules, DNAzymes have proven to be entirely compatible with DNA amplification. Several approaches are then discussed, which relay the activity of an analyte‐activated DNAzyme into the production of massive amounts of DNA amplicons, via "rolling circle amplification", in biosensing applications designed to deliver very high levels of detection sensitivity. Abstract : DNAzymes are single‐stranded DNA molecules with catalytic activities. They can be isolated from large random‐sequence DNA pools via in vitro selection. Examples of newly reported DNAzymes are introduced and the use of DNAzymes in biosensing applications is discussed, with examples of the incorporation of DNAzymes in DNA‐amplification strategies for bioanalytical applications.